Resistance mechanisms and fitness of pyraclostrobin-resistant isolates of Lasiodiplodia theobromae from mango orchards - He, Rui; Yang, Ye; Hu, Zhizhong; Xue, Ru; Hu, Yajuan (PLOS ONE, 2021)
Background Stem-end rot, caused by Lasiodiplodia theobromae (Pat.) Griffon & Maubl is a serious postharvest disease in mango. In China, a high prevalence of the QoI fungicides resistance has been reported in the last decade. The study aimed to discuss factors determining rapid development of pyraclostrobin-resistance and its resistance mechanisms. Methods To determine the resistance stability and fitness of pyraclostrobin resistance in L. theobromae, three phenotypes of pyraclostrobin resistance were compared and analyzed for the EC50 values, mycelial growth, virulence and temperature sensitivity and osmotic stress sensitivity. The relative conductivity and enzyme activities of different phenotypes were compared under fungicide stress to explore possible biochemical mechanisms of pyraclostrobin resistance in L. theobromae. The Cytb gene sequences of different phenotypes were analysed. Results All isolates retained their original resistance phenotypes during the 10 subcultures on a fungicide-free PDA, factor of sensitivity change (FSC) was approximately equal to 1. The resistance-pyraclostrobin of the field isolates should be relatively stable. Two pyraclostrobin-resistant phenotypes shared similar mycelial growth, virulence and temperature sensitivity with pyraclostrobin-sensitive phenotype. After treated by pyraclostrobin, the relative conductivity of the sensitive phenotype was significantly increased. The time of Pyr-R and Pyr-HR reached the most conductivity was about 8–10 times than that of Pyr-S, the time for the maximum value appearance showed significant differences between sensitive and resistant phenotypes. The activities of Glutathione S-transferase (GST), catalase (CAT) and peroxidase (POD) of Pyr-HR were 1.78, 5.45 and 1.65 times respectively, significantly higher than that of Pyr-S after treated by 200 mg/l pyraclostrobin. Conclusion The results showed that the pyraclostrobin-resistant phenotypes displayed high fitness and high-risk. The nucleotide sequences were identical among all pyraclostrobin-resistant and -sensitive isolates. The pyraclostrobin resistance was not attributable to Cytb gene alterations, there may be some of other resistance mechanisms. Differential response of enzyme activity and cell membrane permeability were observed in resistant- and sensitive-isolates suggesting a mechanism of metabolic resistance.